An unique microwave-assisted approach for synthesis of nanosized Fe3O4 as a catalyst in transfer hydrogenation of furfural - Bhatkar, Akash; Yadav, Akash; Gehlot, Bhavika; Rathod, Rutik; Mane, Samruddhi; Gawande, Vaishnavi; Bhosale, Hrtivik; Raja, Thirumalaiswamy; Bhatte, Kushal D. (Research on Chemical Intermediates, 2025)
In this manuscript, we report an unique, one pot, one step synthesis of Fe3O4 nanoparticles. The protocol for synthesis of nanosized Fe3O4 was developed using only Benzyl Amine and Fe(II)acetate precursor via microwave route. Microwave route enables the synthesis of Fe3O4 nanoparticles in short duration and eliminates the need of several chemicals. These salient features make the entire synthetic process environment benign as per green chemistry principles. The morphology and other properties of synthesized nanoparticles were studied by using X-ray diffraction (XRD), X-ray photoelectron spectroscopy analysis (XPS), Raman spectroscopy, Field Emission Scanning Electron Microscopy (FE-SEM), and High-Resolution-Transmission Electron Microscopy (HR-TEM). As-synthesized Fe3O4 nanoparticles exhibit efficient catalytic transfer hydrogenation of furfural using isopropanol as the solvent and hydrogen source, and provide furfuryl alcohol in good yield. This nanosized Fe3O4 was easily removable using magnet and exhibits good reusability. It is observed that acidic-basic sites of nanosized Fe3O4 play a vital role in catalytic transfer hydrogenation reaction.
Keywords: catalytic transfer hydrogenation; Furfural to furfuryl alcohol; green synthesis; Magnetically separable catalyst; Nanosize Fe3O4